The influence of national games on the psychological health of adolescents. (Journal of Educational Sciences, 2016)
The article discusses the history of the origin of the game and its role in the development of the adolescent psyche. Discusses game theory foreign researchers K. Gross, Shern, I. Kant, K. Bullerf, Beitendeik, Z. Freud and other of philosophical-psychological approach. Approved fundamental difference in understanding the meaning and psychological content of the game A. Freud, M. Klein and K. Levin. Discusses the structure of the game. Of great importance is betrayed didactic games. They are given detailed characteristics are different classifications, including educational content. Offers guidelines on the compilation of didactic games and analyze their quality. A special place in the national games as a source of physical, intellectual, and emotional development. Describing national games, theauthors are influencing the intellectual development of the child’s personality: «Aksuek», «Hantalapai», «Arkan Tartys», «Nine kumalak», «Asyk game», «Altybakan». In the table provided the comparison game «Asuk» with computer games and shows the advantage of the national games, their positive effects on the psychological health of modern teenagers.
Keywords: game; educational games; computer games; national games; the views of the national games.